Fases de plastocrono e modelagem do desenvolvimento na cultura da soja - Dalla Porta, Felipe Schmidt (2023)
Crop models for soybean are widely used to understand the interactions between plant and environment, but no model has been developed for edaphoclimatic conditions and cultivars grown in Brazil. The aim of this study was to improve understanding of the basic processes that govern soybean vegetative development and to develop a robust mathematical model to simulate soybean phenology. The study was carried out based on experiments from the 2010/11 to 2022/23 growing seasons in Brazil. The vegetative development was evaluated by detailing the plastochron for a better understanding of the node emission process during the overlapping of the vegetative and reproductive phases. Cultivars with determinate growth habit were divided into two phases, the early plastochron (from the first visible node, pair of unifoliate leaves, to the R1 stage) and the late plastochron (R1 to R3 stage). For cultivars with indeterminate growth habit, the plastochron was divided into three phases: early plastochron (from the first visible node, pair of unifoliate leaves, to the R1 stage), the intermediate plastochron (R1 to the R3 stage) and the late plastochron (R3 to stage R5). The plastochron showed a difference during emission of nodes in soybean cultivars of determinate and indeterminate growth habit under different water regimes. Soybean cultivars of determinate and indeterminate growth habit showed differences between irrigated and rainfed crops. Irrigated cultivars of determinate growth habit show two plastochron phases, the early phase of 59.7 °C day node-1 and the late phase of 65.7 °C day node-1 . In rainfed environments, there is no difference between the early and late phases of plastochron. Cultivars with indeterminate growth habit with irrigation have an average early and late plastochron of 64.1 °C day node-1 , unlike the intermediate phase where the plastochron is 58.5 °C day node-1 . In rainfed environments, the early and intermediate phases have an average value of 60.6 °C day node-1 , unlike the late phase with a plastochron of 79.4 °C day node-1 . The genuinely Brazilian process-based mathematical model for simulating soybean crop development, SimulaSoja, was built. Studies will continue the development of SimulaSoja over the next four years, with calibration and validation processes, with the aim of providing Brazilian producers with a model that represents the genotype x environment interaction in Brazil.